Interstage Weight Gain for Patients with Hypoplastic Left Heart Syndrome Undergoing the Hybrid Procedure. (25th September 2012) - Miller‐Tate, Holly; Stewart, Jamie; Allen, Robin; Husain, Nazia; Rosen, Kerry; Cheatham, John P.; Galantowicz, Mark; Cua, Clifford L.
Abstract Background Weight gain during the interstage (IS) period for hypoplastic left heart (HLHS) patients has been associated with improved outcomes. IS home monitoring has been shown to improve mortality. No data exist on IS weight gain and home monitoring effects on weight gain for HLHS patients undergoing the hybrid procedure. Objective Goal of this study was to describe the weight gain of patients with HLHS undergoing the hybrid procedure during the IS period, to determine if weight parameters were associated with mortality, and to determine if home monitoring improved weight gain. Methods Retrospective review was performed. Patients were included if they had the diagnosis of HLHS and underwent hybrid procedure. Baseline demographics, surgical dates, and all IS weights were recorded. Results Forty‐four patients met inclusion criteria, 24 patients had IS monitoring. Time period evaluated was from April 2006 to June 2011. Mean birth weight of the total population was 3.13 ± 0.61 kg, age at hybrid was 5.84 ± 4.10 days, weight z‐score at hybrid discharge was −1.66 ± 1.01, age at pre‐Stage II was 6.12 ± 1.37 months, IS weight gain was 16.85 ± 5.94 g/day, and weight z‐score pre‐Stage II was −2.25 ± 1.28. Monitored patients had significantly higher weight z‐score pre‐Stage II (−1.67 ± 0.98 vs. −2.82 ± 1.28) and lower change in weight z‐score (−0.26 ± 0.97 vs. −1.24 ± 1.06). Eight patients died IS. There was a significant difference in weight gain per day in those that survived the IS period (17.87 ± 4.75 g/day vs. 12.28 ± 8.65 g/day). There were no significant differences in weight characteristics in patients that survived the Stage II procedure (n = 28) vs. those that did not (n = 7). Conclusion Home monitoring improved IS weight gain in patients undergoing the hybrid procedure. Decreased weight gain per day was associated with IS mortality.